Variação geográfica de Osteocephalus taurinus Steindachner, 1862 (Amphibia : Anura : Hylidae) - ESTUPIÑÁN-TRISTANCHO, Ruth Amanda (Universidade Federal do Pará, 2013)
Osteocephalus taurinus is an Amazonian and Orinochian nominal species with a wide geographic distribution. Its great morphologic variation has suggested that O. taurinus is in fact a species complex. This study examines the geographic variation of morphometric and morphologic characters. The species complex hypothesis is tested. Simultaneously, in order to explain the present body form distribution by biogeographic, rainfall and ecological patterns previously established for Amazonia, these patterns were assessed. From total 431 specimens studied, 16 populations were selected for analysis 20 of inner anatomic structures, 14 morphometric and 6 morphologic external characteres. Statistical analyses and isoline maps indicated that O. taurinus not is a especies complex and exist a interpopulation and intrapopulation variation on the morphometry and morphology of O. taurinus. Polymorphic anatomical characters ocurrs in this species. The first axis of a principal component analysis showed a clinal variation of body size along the entire geographic distribution was most plainly evident in males. Clinal variaton in other characters studied was independent of cline. Spatial size distribution indicated the largest specimens occur in the Amazon lands low, where rainforest vegetation divides savanna areas to the north and south of South America. These two last areas more often presented the smaller forms. In this study, the distribution observed for O. taurinus was not explained by traditional divisions of Amazonia, and suggest some noise generated by high intrapopulational variation. This spatial model of O. taurhius body size did not show a pattern of isolation by distance, which may suggest a recent arca colonization by this species. Simultaneusly, the study confirms the early Pliocenic origin hypothesis for Osteocephalus, which allowed O. taurinus had time to disperse before the Andes emerged as a geographical barrier.